Modulation of transcription by DNA supercoiling: a deletion analysis of the Escherichia coli gyrA and gyrB promoters. - Menzel, R (1987)
Expression of the genes determining the subunits of Escherichia coli DNA gyrase (gyrA and gyrB) is known to be induced by relaxation of the template DNA. In this paper we report a deletion analysis of the gyrA and gyrB promoter regions. We find that a DNA sequence 20 base pairs long that includes the -10 consensus region, the transcription start point, and the first few transcribed bases is responsible for the property of induction by DNA relaxation. We propose a model for relaxation-stimulated transcription in which promoter clearance is the rate-limiting step.